2008
DOI: 10.1021/ja7100399
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Crystallization Mechanism, and Catalytic Properties of Titanium-Rich TS-1 Free of Extraframework Titanium Species

Abstract: A new route to the synthesis of TS-1 has been developed using (NH4)2CO3 as a crystallization-mediating agent. In this way, the framework Ti content can be significantly increased without forming extraframework Ti species. The prepared catalyst had a Si/Ti ratio as low as 34 in contrast to the ratio of 58 achieved with the methods A and B established by the Enichem group (Clerici, M. G.; Bellussi, G.; Romano, U. J. Catal. 1991, 129, 159) and Thangaraj and Sivasanker (Thangaraj, A.; Sivasanker, S. J. Chem. Soc.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
304
2
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 349 publications
(323 citation statements)
references
References 70 publications
13
304
2
4
Order By: Relevance
“…The catalytic performance of these transition metal-containing materials depends largely on their composition and structure. A deep understanding of the active sites and the formation mechanism in these materials is helpful for the development of catalysts with high selectivity and activity [36,37]. However, due to the low concentration of transition metal ions (\2 %), it is difficult to obtain definite information on the transition metal ions in these materials [31], such as their coordination environments and distributions.…”
Section: Uv Raman Spectroscopic Characterization Of Transition Metal-mentioning
confidence: 99%
See 2 more Smart Citations
“…The catalytic performance of these transition metal-containing materials depends largely on their composition and structure. A deep understanding of the active sites and the formation mechanism in these materials is helpful for the development of catalysts with high selectivity and activity [36,37]. However, due to the low concentration of transition metal ions (\2 %), it is difficult to obtain definite information on the transition metal ions in these materials [31], such as their coordination environments and distributions.…”
Section: Uv Raman Spectroscopic Characterization Of Transition Metal-mentioning
confidence: 99%
“…As a highly active and selective catalyst, TS-1 has been widely used in a number of oxidation reactions with H 2 O 2 as oxidant under mild conditions [32,33,37]. However, there are still many issues under debate, such as what's the exact nature of the active site [36,37,68,69] and the reaction pathways [70][71][72][73].…”
Section: In Situ (Uv) Raman Spectroscopic Characterization Of Catalytmentioning
confidence: 99%
See 1 more Smart Citation
“…TS-1 was chosen as a standard titanosilicate zeolite catalyst with an MFI-type structure containing three-dimensional 10-membered ring (3D 10-MR) pores 22) . Ti-MWW was prepared as an MWW-type structure containing two types of ring: 12-MR pores with a system of independent 10-MR channels 23) .…”
Section: Recyclable Titanosilicate Zeolite Catalyst Formentioning
confidence: 99%
“…Herein, two lines of available evidence can be presented to explain the different behavior between Au/Ti-HMS and Au/TS-1. For one thing, it has been reported that TS-1 is a type of hydrophobic material, 30 which exhibits an obvious wettability and adsorbability for methanol over water. Therefore, in methanol/water solvent or pure methanol, a number of the active centers on Au/TS-1 would be covered by the adsorbed methanol molecule, resulting in the decrease of catalytic performance.…”
mentioning
confidence: 99%